2016
DOI: 10.1073/pnas.1601440113
|View full text |Cite
|
Sign up to set email alerts
|

Postretrieval new learning does not reliably induce human memory updating via reconsolidation

Abstract: Reconsolidation theory proposes that retrieval can destabilize an existing memory trace, opening a time-dependent window during which that trace is amenable to modification. Support for the theory is largely drawn from nonhuman animal studies that use invasive pharmacological or electroconvulsive interventions to disrupt a putative postretrieval restabilization ("reconsolidation") process. In human reconsolidation studies, however, it is often claimed that postretrieval new learning can be used as a means of "… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 46 publications
2
49
1
1
Order By: Relevance
“…However, our study joins a growing number of other studies showing failures to replicate the reconsolidation effect using behavioural manipulations (e.g. Golkar, Bellander, Olsson, & Öhman, 2012; Hardwicke, Taqi, & Shanks, 2016; Kindt & Soeter, 2013; Soeter & Kindt, 2011; Wichert et al, 2011) or pharmacological manipulations (e.g. Bos, Beckers, & Kindt, 2014; Wood et al, 2015).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…However, our study joins a growing number of other studies showing failures to replicate the reconsolidation effect using behavioural manipulations (e.g. Golkar, Bellander, Olsson, & Öhman, 2012; Hardwicke, Taqi, & Shanks, 2016; Kindt & Soeter, 2013; Soeter & Kindt, 2011; Wichert et al, 2011) or pharmacological manipulations (e.g. Bos, Beckers, & Kindt, 2014; Wood et al, 2015).…”
Section: Discussionsupporting
confidence: 61%
“…Bos, Beckers, & Kindt, 2014; Wood et al, 2015). The study of Hardwicke et al (2016) makes a particularly strong case against reconsolidation effects in humans, because it attempted to directly and conceptually replicate the results of a study that has been frequently referred to as a convincing demonstration of human reconsolidation in procedural memory (Walker, Brakefield, Hobson, & Stickgold, 2003), but was unsuccessful in seven experiments. Hardwicke et al did not find any evidence for the impairment effects predicted by reconsolidation theory.…”
Section: Discussionmentioning
confidence: 99%
“…A similar situation exists for instrumental memories: some studies have shown that instrumental memories undergo post-retrieval modification (Fuchs, Bell, Ramirez, Eaddy, & Su, 2009;Milton, Lee, Butler, Gardner, & Everitt, 2008), while others have not (Hernandez & Kelley, 2004). The literature on post-retrieval modification of human procedural memories has also been recently thrown into doubt (Hardwicke, Taqi, & Shanks, 2016). There are many differences between these studies that could account for such discrepancies, including the type of amnestic agent, how the amnestic agent is administered (systemically or locally), the type of reinforcer, and the timing of stimuli.…”
Section: Resultsmentioning
confidence: 91%
“…If memory reactivation combined with pharmacological or non-pharmacological treatment does not reliably induce any memory impairment, then the rationale for clinical exploitation may be flawed. As a recent example, the original demonstration that human motor memory could be disrupted by combining memory reactivation with interference [13] was not replicated in a series of direct and conceptual replication attempts within a single extensive study [71]. While perhaps it remains unclear whether human motor memories undergo reconsolidation, there are very many studies showing reconsolidation effects in other settings [72], particularly for fear memories.…”
Section: The Reliability Of Reconsolidation Effectsmentioning
confidence: 99%